The stages of memory: reflections on memorial art, loss, and the spaces between - Young, James Edward (Public history in historical perspective, 2016)
Introduction. The memorial's vernacular arc between Berlin's Denkmal and New York City's 9/11 Memorial -- The stages of memory at Ground Zero: the National 9/11 Memorial process -- Daniel Libeskind and the houses of Jewish memory: what is Jewish architecture? -- Regarding the pain of women: gender and the arts of holocaust memory -- The terrible beauty of Nazi aesthetics -- Looking into the mirrors of evil: Nazi imagery in contemporary art at the Jewish Museum in New York -- The contemporary arts of memory in the works of Esther Shalev-Gerz, Miroslaw Balka, Tobi Kahn, and Komar and Melamid -- Utøya and Norway's July 22 memorial: the memory of political terror